ULTRASOUND GUIDED ERECTOR SPINAE BLOCK VERSUS THORACIC EPIDURAL ANALGESIA FOR ACUTE POST THORACOTOMY PAIN RELIEF (The Research of Medical Science Review, 2025)
Background: Thoracic surgery, especially thoracotomy, is associated with significant postoperative pain. Effective pain management is essential for patient recovery. Recent studies suggest that ultrasound-guided erector spinae plane (ESP) block could be an effective alternative to traditional thoracic epidural analgesia (TEA) for regional analgesia in thoracic surgeries, rib fractures, and breast surgeries. ESP block is known to be technically easier and safer than TEA. Objective: To compare the effectiveness of ultrasound-guided erector spinae plane block (ESP) with thoracic epidural analgesia (TEA) in reducing postoperative pain, as measured by the Visual Analog Scale (VAS), in patients undergoing thoracotomy. Methods: A randomized controlled trial was conducted at the Department of Anesthesiology, LRH Peshawar, from 20th October 2022 to 20th April 2023. A total of 60 patients undergoing thoracic surgery were enrolled. Patients were randomly assigned to two groups: Group A received thoracic epidural analgesia (TEA), and Group B received erector spinae block (ESP). The primary outcome was the post-thoracotomy VAS score, recorded at 24 hours after surgery. Results: The study included 60 patients, with 30 patients in each group. The mean age in Group A was 50.133 ± 6.69 years, and in Group B, it was 49.333 ± 6.63 years. The mean post-thoracotomy VAS score was significantly lower in Group B (3.066 ± 0.74) compared to Group A (5.866 ± 0.97), with a p-value of 0.000. Conclusion: The study's results align with recent national and international research, highlighting the effectiveness of advanced pain management strategies in reducing post-thoracotomy pain. These findings support the adoption of enhanced recovery protocols in thoracic surgery worldwide.